2009 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2009
DOI: 10.1109/iembs.2009.5333547
|View full text |Cite
|
Sign up to set email alerts
|

Motion classification using epidural electrodes for low-invasive brain-machine interface

Abstract: Brain-machine interfaces (BMIs) are expected to be used to assist seriously disabled persons' communications and reintegrate their motor functions. One of the difficult problems to realize practical BMI is how to record neural activity clearly and safely. Conventional invasive methods require electrodes inside the dura mater, and noninvasive methods do not involve surgery but have poor signal quality. Thus a low-invasive method of recording is important for safe and practical BMI. In this study, the authors us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 13 publications
0
7
1
Order By: Relevance
“…In animal studies, simple motor outputs have been decoded using eECoG. In rats, an eECoG-based decoder was used to classify four types of body movements, achieving an accuracy of 73.2% [28], and the two-dimensional reach direction was decoded with an accuracy of 69% [29].…”
Section: Introductionmentioning
confidence: 99%
“…In animal studies, simple motor outputs have been decoded using eECoG. In rats, an eECoG-based decoder was used to classify four types of body movements, achieving an accuracy of 73.2% [28], and the two-dimensional reach direction was decoded with an accuracy of 69% [29].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the advantages of an invasive approach to BMI (electrocorticography) over scalp EEG (e.g., higher signal bandwidth, closer location to the recording target, higher spatial resolution and signal amplitude, and the lack of interference from both electrooculography and electromyography [with the exception of the reference electrode]), 36 an invasive approach to BMI requires the implantation of a foreign body into the brain parenchyma, 33 which may result in inflammation. With an increase in the cross-sectional area of the device, there is increased inflammation in the week following implantation 29 (most likely due to increased parenchymal damage with insertion).…”
Section: Brain-machine Interfacesmentioning
confidence: 99%
“…In the last few years, placing ECoG grids in the epidural space has been proposed to be a less invasive alternative to subdural grids, with most studies reporting on the decoding of task-related oscillatory activity in rodents (Uejima et al, 2009 ; Slutzky et al, 2010 , 2011 ) or non-human primates (Rouse and Moran, 2009 ; Shimoda et al, 2012 ; Lee et al, 2013 ; Marathe and Taylor, 2013 ; Rouse et al, 2013 ; Williams et al, 2013 ). A few human case studies have also shown the feasibility of epidural recordings for decoding task-related oscillations during short recording sessions (Leuthardt et al, 2006 ; Gomez-Rodriguez et al, 2010 ; Gharabaghi et al, 2014a , b ).…”
Section: Discussionmentioning
confidence: 99%